2022
DOI: 10.3390/cancers14020306
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 Regulates EGFR and Wnt Signaling Pathways and Is a Promising Target for Combinatorial Treatment of Breast Cancer

Abstract: Identifying new therapeutic strategies for triple-negative breast cancer (TNBC) patients is a priority as these patients are highly prone to relapse after chemotherapy. Here, we found that protein arginine methyltransferase 1 (PRMT1) is highly expressed in all breast cancer subtypes. PRMT1 depletion decreases cell survival by inducing DNA damage and apoptosis in various breast cancer cell lines. Transcriptomic analysis and chromatin immunoprecipitation revealed that PRMT1 regulates the epidermal growth factor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Recent cancer-related studies on the role of PRMTs are summarized in Table III. In TNBC, PRMT1 regulates the EGFR and the Wnt signalling pathways (80). Type I PRMT inhibitors decrease breast cancer cell proliferation and have anti-tumour activity.…”
Section: Methylation Of Nonhistonesmentioning
confidence: 99%
“…Recent cancer-related studies on the role of PRMTs are summarized in Table III. In TNBC, PRMT1 regulates the EGFR and the Wnt signalling pathways (80). Type I PRMT inhibitors decrease breast cancer cell proliferation and have anti-tumour activity.…”
Section: Methylation Of Nonhistonesmentioning
confidence: 99%
“…Studies have demonstrated that PRMT1 expression is upregulated in TNBC and contributes to tumor progression and chemotherapy resistance. [ 20 ] Metabric and TCGA databases also indicated that PRMT1 expression is upregulated in breast cancer, especially in TNBC (Figure S4A–C, Supporting Information). We then performed clone formation and MTT assays in TNBC cells before hypoxic treatment and found that the overexpression of PRMT1 could diminish the inhibition of cancer cell proliferation by downregulating circTBC1D14 expression (Figure S4D,E, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Our study demonstrate that PRMT1 suppresses colon cancer, which can provide a more comprehensive knowledge of the underlying mechanisms of PRMT1 in cancer progression. PRMT1 has been known as an oncogene via stimulating cancer cell proliferation or blocking apoptosis [ 36 , 39 ], while the opposite findings have also been reported in some experiments in which PRMT1 might inhibit proliferation and promote apoptosis in cancer [ 37 , 38 ]. Despite of regulating cancer cell proliferation and apoptosis, we provide another mechanism driven by PRMT1, in which PRMT1 inhibits necroptotic cell death.…”
Section: Discussionmentioning
confidence: 99%